Instilling the Values of the Five Souls in Realizing Superior Human Resource Management - Anggara, Fajar Surya Ari; Harahap, Soritua Ahmad Ramdani; Thoriq, Abdul (INOVATOR, 2024)
This study tries to connect the values in the five spirits that exist in Islamic boarding schools with the progress of their human resources. Seeing the development of problems that occur in our younger generation, ranging from acts of violence, brawls and low morals as well as the role of outside culture greatly affects the growth and development of the younger generation. This needs attention so that the younger generation does not fall into bad things and is able to carry out their duties as a superior generation and have character in accordance with the vision of Indonesia 2045. This research uses descriptive qualitative methods, by taking data from relevant journals and books. The results of this study indicate that the cultivation of the five values of the spirit, namely sincerity, modesty, self-sufficient, Islamic brotherhood and freedom is able to produce a superior and quality generation. This is proven by the implementation of these values for all human resources in it.